IMPLEMENTASI PERATURAN MENTERI DALAM NEGERI NOMOR 2 TAHUN 2016 TENTANG KARTU IDENTITAS ANAK: Studi Dinas Kependudukan dan Pencatatan Sipil Kabupaten Lombok Timur - Sulastini (JURIDICA : Jurnal Fakultas Hukum Universitas Gunung Rinjani, 2021)
The government issued Law Number 23 of 2006 concerning Population Administration. One of the government's efforts to provide and protect children's rights to identity is manifested in the issuance of the Child Identity Card (CIC) program which took effect since early 2016. CIC is regulated in the Minister of Home Affairs Regulation Number 2 of 2016 concerning Child Identity Cards. The research objective was to determine the implementation of the Minister of Home Affairs Regulation Number 2 of 2016 regarding CIC in East Lombok Regency and to find out the legal aspects in the implementation of CIC issuance in East Lombok Regency. This research is a type of empirical juridical research, in this study the approach used in solving the problem is to use the empirical juridical approach method. The juridical approach that is meant is that law is seen as a norm or das sollen, because in discussing the problems in this study using legal materials (both written law and unwritten law or both primary, secondary and tertiary legal materials. by looking at law as a social, cultural or das sein reality because in this study the data used are primary data obtained directly from the research location. In this study the type of data collected is divided into two types of data, namely primary data and secondary data. Data collection techniques obtained directly from data sources at the research location or field (field research) were obtained through interviews and observations.